Efficacy of Mycophenolate in Interstitial Lung Disease Associated with Rheumatoid Arthritis - Sindhuja Rajendran; Ashish Jacob Mathew; John Mathew; Ruchika Goel (Journal of Clinical Rheumatology and Immunology)
Background: Interstitial lung disease (ILD) is a significant cause of mortality in patients with Rheumatoid Arthritis (RA). Existing studies on the efficacy of Mycophenolate (MPA) for RA-associated ILD are limited, with the largest study including only 26 patients. This study aims to evaluate the efficacy of MPA in stabilizing or improving lung function in a larger cohort of RA-ILD patients over an extended follow-up period. Methods: Patients diagnosed with RA-ILD and treated with MPA for [Formula: see text] 1year, attending our clinics between 2017 and 2023 were included. Data regarding demography, spirometry, HRCT and treatment were noted retrospectively at the diagnosis of ILD (baseline) and 6 monthly visits thereafter till last follow up. Data were collected on patient demographics, spirometry, high-resolution CT (HRCT) scans, and treatment regimens. The primary outcome was the change in predicted forced vital capacity (FVC) over the follow-up period, with a [Formula: see text] 10% decline considered as progression. Clinical improvements in cough, dyspnea, and HRCT findings were recorded as binary outcomes. Results: Of the 73 patients (58 females), 70% showed stability or improvement in FVC, while 18% experienced a decline. Clinically, 86% of patients improved or remained stable, while 12% worsened. HRCT results showed stable or improved disease in 34% of patients, 30% had worsening of fibrosis, while 36% did not undergo follow-up HRCT due to clinical stability. Physiologically - 52(70%) met the primary outcome of stability/ improvement in % FVC while 18% had worsening in % FVC. Use of rituximab was not associated with better outcomes. None of the baseline clinical parameters predicted better outcomes in univariate. The most common adverse events were dyspepsia and serious infections, occurring in 12% of patients Conclusion: MPA is an effective and relatively safe treatment option for RA-ILD, with 70% of patients achieving stabilization or improvement in lung function.